Psikologi Olahraga dan Filsafat - Dian Anggraini Kusumajati (Humaniora, 2012)
The awareness that sports was an international science that emerged in the mid of 20th century, and in Indonesia it was officially acknowledged in 1998 by an sport science declaration. The application of psychology in sports was to support the sport talent in a person could be well developed without any constraints in his/her personality. Eksistensialisme  is a branch of the Phylosophy that reflects that men always exists in his/her life. Phylosophgy played important role in integrating many science reviews that could be formulated in sports having ontology, episthemology, and axiology dimensions which was in line with other sciences. Sport Psychology and Phylosophy reviews reveal the importance of the “root” of them in order to develop it, as well as to introduce sport psychology in Indonesia.